The efficiency of the Heterogeneous Photo-Fenton Process for Methyl Orange Degradation: A Review - Fatmawati, Rani; Dewata, Indang; Nasra, Edi; Away, Romy Dwipa Yamesa (Jurnal Pijar Mipa, 2025)
Methyl orange dye is an organic pollutant often found in textile industry waste and harms the environment due to its nature, which makes it difficult to decompose naturally. One method that has attracted attention in its processing is the Photo-Fenton process, which utilizes hydroxyl radicals (•OH) as powerful degradation agents. This article summarizes recent developments in applying heterogeneous Photo-Fenton to Methyl Orange degradation, focusing on degradation efficiency, factors influencing reactions, and degradation pathways. This study discusses the influence of reaction parameters such as initial pH, H₂O₂ concentration, catalyst concentration and light intensity on the degradation rate. In addition, various types of heterogeneous catalysts, including metal oxide-based and ferrous composites, were analyzed based on their effectiveness and stability in the Photo-Fenton system. The Methyl Orange degradation pathway is proposed based on an intermediate product identified in previous studies, suggesting that the reaction proceeds through a gradual oxidation mechanism until simpler and more environmentally friendly compounds are formed. The results of this study show that the heterogeneous Photo-Fenton system provides advantages over homogeneous systems, especially in increasing degradation efficiency and prolonging the catalyst reactivity cycle. The use of heterogeneous catalysts allows for the formation of larger numbers of active species, thus accelerating the breaking of the Methyl Orange structure. In addition, further research is needed to improve the stability of the catalyst, optimize reaction conditions, and evaluate its potential application on an industrial scale. This study will be a reference for developing a more efficient and sustainable Photo-Fenton-based waste treatment method.